PERBEDAAN BERAT BADAN ANAK UMUR 1-3 TAHUN PADA KELUARGA DENGAN JUMLAH 1 BALITA DAN LEBIH DARI 1 BALITA - UTAMI, WIWIK; MULYANI, SRI; Muslima, Evita (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2017)
The number of children in one family lot can lead to the child's weight is less. Phenomena that exist on the Village showed Kedungrejo toddler skinny-skinny body are in families with children under five is more than 1, while toddlers thin body does not mean being in a family that only has 1 toddler. This study aims to determine the differences in the weight of children aged 1-3 years in the Village District of Sumberrejo Kedungrejo Bojonegoro.Design analytical research using cross sectional approach to the entire population of toddlers aged 1-3 years in as many as 93 villages Kedungrejo toddlers. The total sample of 74 respondents, non-probability sampling technique sampling with purposive sampling. Data processing using editing, coding, scoring and tabulating and analyzing the test of independent sample t test.The results of the study respondents ie 74 of 34 respondents who are in families with number 1 toddler found that a child's weight as much as 6 Children underweight (16.2%), and of the 34 respondents who are in families with more than 1 toddler gained weight children were underweight were 11 children (30%). Then from the results of independent sample t test with a significant p value (0.076)> ? (0.050) which means that Ho is accepted, which means there is no difference in the weight of children aged 1-3 years in the number of families with more than 1 toddler and 1 toddler.It can be concluded that the weight of children aged 1-3 years in the number of families with more than 1 toddler and 1 toddler the same.